Subcutaneous parasitic infection in Slovenia - Bartenjev, Mark Sergej (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2022)
Filariasis is a parasitic disease caused by infection with roundworms of the Filarioidea superfamily. Depending on the species of roundworm, the disease can present itself in one of three forms. It can affect the lymphatic system, the subcutaneous tissue, or serous cavities. We present the case of a male patient from central Europe with a subcutaneous manifestation similar to filariasis. Laboratory findings showed eosinophilia and elevated levels of IgE antibodies, and histological examination of skin biopsy material showed granulation tissue with lymphoid and plasma cell infiltration. When the lesion was examined under a microscope following an excision, live wormlike parasites about 3.5 cm long were detected. Such parasitic infections are usually encountered in tropical regions and sometimes reported in travelers returning from endemic countries. Our patient, however, had never left Europe, which is what makes this case so interesting.
Keywords: dermatologija; dermatology; Dirofilaria; filariasis; filarioza